2021
DOI: 10.3389/fvets.2021.688611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Antimicrobial Peptide Plectasin on the Growth Performance, Intestinal Health, and Immune Function of Yellow-Feathered Chickens

Abstract: The goal of the study was to test the effects of an antibiotic substitute, plectasin, on the growth performance, immune function, intestinal morphology and structure, intestinal microflora, ileal mucosal layer construction and tight junctions, ileal immune-related cytokines, and blood biochemical indices of yellow-feathered chickens. A total of 1,500 one-day-old yellow-feathered chicks were randomly divided into four dietary treatment groups with five replicates in each group and 75 yellow-feathered chicks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…than broilers fed control diets (32). Zhang et al reported that dietary antimicrobial peptide plectasin significantly decreased the quantity of E. coli and increased the ratio between Lactobacilli and E. coli in the ileal contents of 21-day-old yellow-feathered chickens (16). Tang et al also reported that the antimicrobial peptide lactoferrin significantly decreased the number of E. coli and increased the number of Lactobacilli and Bifidobacterium in the ileum, caecum, and colon of weaned piglets (70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…than broilers fed control diets (32). Zhang et al reported that dietary antimicrobial peptide plectasin significantly decreased the quantity of E. coli and increased the ratio between Lactobacilli and E. coli in the ileal contents of 21-day-old yellow-feathered chickens (16). Tang et al also reported that the antimicrobial peptide lactoferrin significantly decreased the number of E. coli and increased the number of Lactobacilli and Bifidobacterium in the ileum, caecum, and colon of weaned piglets (70).…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of intestinal epithelial barrier and intestinal microecology caused by Paneth cell dysfunction is one of the important pathogenies of inflammatory bowel diseases, such as Crohn's disease and colitis (15). AMPs have important application value in the poultry industry and were reported to have beneficial effect on growth performance, nutrient digestibility, immune functions, and intestinal morphology, integrity, and microflora in broilers (16)(17)(18). Hence, AMPs can be potential antibiotic alternatives, which have attracted researchers' interests.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Studies have shown that soybean polypeptides contain antibodies that enhance animal immune function and improve animal health ( 23 ). Small peptides can participate in the immune regulation of the body and promote the phagocytosis of macrophages, lymphocyte and immature splenic cell proliferation which may be the reason for the increase of serum immune level ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…With an 80-year application history, AMPs are considered strong candidates to replace antibiotics in the animal food production industry and have been widely studied [ 201 ]. For example, broiler feed supplemented with the bacteriocin microcin J25 improved performance, reduced systemic inflammation, improved fecal microbiota (lower population of total anaerobic bacteria), and decreased Salmonella infection rate [ 202 ]. Similar beneficial effects have been observed with the use of AMPs in piglet feed [ 201 , 203 , 204 , 205 ].…”
Section: Alternatives To Antibiotics As Growth Promotersmentioning
confidence: 99%
“…Although the antimicrobial activity of AMPs plays an important role in their impact on animal growth, their ability to modulate the immune response also strongly contributes to their beneficial effects. It has been shown that supplementation of feed with microcin J25, a bacteriocin active against several E. coli and Salmonella strains, can promote growth performance, improve intestinal morphology, influence fecal microbiota composition, and reduce the secretion of pro-inflammatory factors (IL-1β, TNF-α, IL-6) in broilers [ 202 ]. It was also observed that microcin J25 was able to attenuate intestinal inflammation diseases caused by enteric pathogens [ 207 ].…”
Section: Alternatives To Antibiotics As Growth Promotersmentioning
confidence: 99%